Inhibition of Cdc42 activity extends lifespan and decreases circulating inflammatory cytokines in aged female C57BL/6 mice. Issue 9 (4th August 2020) - Florian, Maria Carolina; Leins, Hanna; Gobs, Michael; Han, Yang; Marka, Gina; Soller, Karin; Vollmer, Angelika; Sakk, Vadim; Nattamai, Kalpana J.; Rayes, Ahmad; Zhao, Xueheng; Setchell, Kenneth; et al.
Abstract: Cdc42 is a small RhoGTPase regulating multiple functions in eukaryotic cells. The activity of Cdc42 is significantly elevated in several tissues of aged mice, while the Cdc42 gain‐of‐activity mouse model presents with a premature aging‐like phenotype and with decreased lifespan. These data suggest a causal connection between elevated activity of Cdc42, aging, and reduced lifespan. Here, we demonstrate that systemic treatment of aged (75‐week‐old) female C57BL/6 mice with a Cdc42 activity‐specific inhibitor (CASIN) for 4 consecutive days significantly extends average and maximum lifespan. Moreover, aged CASIN‐treated animals displayed a youthful level of the aging‐associated cytokines IL‐1β, IL‐1α, and INFγ in serum and a significantly younger epigenetic clock as based on DNA methylation levels in blood cells. Overall, our data show that systemic administration of CASIN to reduce Cdc42 activity in aged mice extends murine lifespan. Abstract : The activity of the small RhoGTPase Cdc42 is significantly elevated in blood of elderly humans and in several tissues of aged mice. Cdc42 constitutive activation induces premature aging and decreases murine lifespan. Here, we show that systemic treatment of aged (75‐week‐old) female C57BL/6 mice with a Cdc42 activity‐specific inhibitor (CASIN) for 4 consecutive days significantly extends average and maximum lifespan, reduces levels of IL‐1b, IL‐1a, and INFg aging‐associated cytokines in serum, and rejuvenates the biological epigenetic clock as based on DNA methylation levels in blood cells.